Innovation teaching method in primary education - Munira Kadirova Rasulovna; G’ulomova Mushtariybonu Mo’ydinjon qizi (Peerian Journals Publishing, 2022)
Nowadays, primary education is the foremost and basic right of every child. It is the first step in making of the character of child. The role of primary education is to ensure broad based learning of the child. This includes development of social, cognitive, cultural, emotional and physical skills. This education should be delivered keeping information and entertainment hand in hand. On the other hand, primary school should aim at providing rich, stimulating and caring environment in which the child feels happy, safe, secure and confident. Learning at this young age should give birth to creative and enquiring minds
Keywords: primary school; Creative Teaching